(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
The article presents Mapiko masks from Mozambique and discusses the relationships that theater and dance groups establish with such a tradition in the current scenic context in the city of Maputo. Mapiko masks are traditional to the Makonde people who live in the north of Mozambique. Mapiko underwent several modifications and adaptations over the years, dialoguing with other ethnic groups, European colonial references and political and ideological transformations. This article presents such transformations and possibilities that such a mask has been assuming over the years, in order to discuss the relationship between tradition and contemporaneity in the use of masking influenced by Mapiko in the current scene of Maputo.